2009
DOI: 10.1007/s11113-009-9133-x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Community in Disaster Response: Conceptual Models

Abstract: We focus on the role that community plays in the continuum of disaster preparedness, response and recovery, and we explore where community fits in conceptual frameworks concerning disaster decision-making. We offer an overview of models developed in the literature as well as insights drawn from research related to Hurricane Katrina. Each model illustrates some aspect of the spectrum of disaster preparedness and recovery, beginning with risk perception and vulnerability assessments, and proceeding to notions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
122
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(131 citation statements)
references
References 22 publications
6
122
0
3
Order By: Relevance
“…But, with the introduction of various national strategies (e.g., National Disaster Recovery Framework, National Health Security Strategy, National Security Strategy) as well as international frameworks [e.g., Sendai Framework, Hyogo Framework for Action (United Nations Office for Disaster Risk Reduction, 2005Reduction, , 2015], these approaches have evolved to use risk analysis to identify, assess, and address a range of social, behavioral, and ecological factors that not only contribute to vulnerability but can be leveraged to mitigate or adapt to those stresses (O'Sullivan, Kuziemsky, Toal-Sullivan, & Corneil, 2013;Paton, Parkes, Daly, & Smith, 2008). These fields of emergency management and disaster risk reduction also began to embrace a fuller appreciation of the range of actors involved in response and recovery, namely civil society organizations working alongside government stakeholders (Eikenberry, Arroyave, & Cooper, 2007;Patterson, Weil, & Patel, 2010). More recently, this approach to leverage community strengths for resilience is being applied to the resettlement of whole communities in an effort to adapt to climate change.…”
Section: Definitions and Drivers Of Resiliencementioning
confidence: 99%
“…But, with the introduction of various national strategies (e.g., National Disaster Recovery Framework, National Health Security Strategy, National Security Strategy) as well as international frameworks [e.g., Sendai Framework, Hyogo Framework for Action (United Nations Office for Disaster Risk Reduction, 2005Reduction, , 2015], these approaches have evolved to use risk analysis to identify, assess, and address a range of social, behavioral, and ecological factors that not only contribute to vulnerability but can be leveraged to mitigate or adapt to those stresses (O'Sullivan, Kuziemsky, Toal-Sullivan, & Corneil, 2013;Paton, Parkes, Daly, & Smith, 2008). These fields of emergency management and disaster risk reduction also began to embrace a fuller appreciation of the range of actors involved in response and recovery, namely civil society organizations working alongside government stakeholders (Eikenberry, Arroyave, & Cooper, 2007;Patterson, Weil, & Patel, 2010). More recently, this approach to leverage community strengths for resilience is being applied to the resettlement of whole communities in an effort to adapt to climate change.…”
Section: Definitions and Drivers Of Resiliencementioning
confidence: 99%
“…The findings could be attributed to a more cooperative behavior in part of some non-government organizations than in the government. Patterson et al (2010) reported that well-functioning community organizations have the trust of their members and possess the moral authority to urge cooperative behavior that the government lacks. The result of this study is in contrast with the findings of Fowler et al (2007) in which public government employees expressed the highest level of perceived preparedness for coping with a major crisis or disaster while non-government employees expressed the lowest perception of being prepared.…”
Section: Resultsmentioning
confidence: 99%
“…Such an approach would confirm the contribution to adaptive capacity within systems by civic ecological intervention, something which has hitherto only been described through individually selected case studies (e.g. Holland, 2004;Kingsley et al, 2009;Patterson et al, 2010;Green and Philips, 2013;Krasny and Tidball, 2015). Such studies, although insightful, fail to describe innovative stakeholder-led action as a coherent phenomenon exercising influence throughout landscapes and their associated social-ecological systems.…”
Section: Social-ecological Innovation In Urban Areasmentioning
confidence: 95%